Importance of a role of (EuN3)2+ complex generated in the Eu3+/N3-/H2O2 system studied by the chemiluminescent method - K. Staninski; M. Kaczmarek; S. Lis; M. Elbanowski (International Journal of Photoenergy)
Chemiluminescence has been studied in the systems containing hydrogen peroxide H2O2 and Eu3+ and N3- ions. Ultraweak emission lasting for a few tens of hours has been observed. The dominant bands in the spectral distribution of the chemiluminescence are those of λ=594 and 620 nm,which proves that excited Eu3+ ions are the only emitters in the system. As follows from measurements of chemiluminescence intensity for different pH of the solution and concentration of F- ions,introduced as ligands competitive to N3- ,it is in direct proportion to the concentration of the (EuN3)2+ complex forming in the solution.